Optimizing fish meal-free commercial diets for Nile tilapia, Oreochromis niloticus - Koch, Joao Fernando [UNESP] (2016)
A feeding trial was conducted in a closed recirculating aquaculture system with Nile tilapia Oreochromis niloticus juveniles (mean weight, 6.81. g) to examine the response to a practical diet containing protein primarily from menhaden fish meal (FM) and soybean meal (SBM) (control, Diet 1) or to diets with decreasing ratios of PBM to SBM (Diets 2-7; dose-response) as a total replacement for digestible protein from FM, and the efficacy of 1% supplemental taurine (Tau) at the highest level of plant protein inclusion by removing Tau (Diet 8). To the extent possible, the replacement diets were formulated using currently published amino acid availabilities for the ingredients of interest in order to estimate and supplement the first two limiting amino acids (Met and Lys) to match levels in the FM control diet. The test diets were formulated to contain 35% digestible protein. Fish were fed three times daily all they would consume in 30 min. All performance measures were quadratic with respect to PBM:SBM ratio in the diet. The highest weight gain, lowest average daily feed intake, lowest feed conversion, and greatest specific growth rate coincided with a dietary PBM:SBM ratio of 1.22 to 1.35 suggesting that the best tilapia performance in the current trial was achieved with replacement formula D3 that contained approximately 20% SBM, 30% PBM, and supplemental Lys, Met, and Tau. However, all growth performance measures were significantly linear and decreased with respect to increasing distance from the ideal protein amino acid profile for tilapia. Positive effects of taurine supplementation at the highest level of dietary plant protein inclusion were not observed and may have been overwhelmed by imbalances in other amino acids in the test diets. The current results provide evidence that total deviation from the ideal protein profile in tilapia is an important consideration for diet formulation when combinations of diet ingredients are used. Hence, the essential amino acid content of a fish meal control diet may be an inadequate target for optimizing fish meal replacement diets for tilapia; whereas the whole body or muscle amino acid pattern may be a more useful formulation target. Finally, while the database of ingredients that have been evaluated in tilapia is growing, the industry will benefit from more efficient diets as long-term averages of amino acid composition and digestibility accrue for a variety of traditional and novel ingredients. Statement of Relevance: The current results provide evidence that it is the total deviations from a postulated ideal protein profile that is a more important consideration for diet formulation than the combination of diet ingredients used to meet that profile. Therefore, it should be possible to formulate least-cost fish meal replacement diets for tilapia, irrespective of ingredient combinations, and diet intact protein level, as long as a reasonable amino acid model is chosen and a fairly robust set of ingredient composition and digestibility data are available.